Cytoplasmic mislocalization and mitochondrial colocalization of TDP-43 are common features between normal aged and young mice. Issue 17 (November 2020) - Termsarasab, Pichet; Thammongkolchai, Thananan; Gao, Ju; Wang, Luwen; Liang, Jingjing; Wang, Xinglong
Transactive response DNA binding protein 43 (TDP-43) pathologies have been well recognized in various neurodegenerative disorders including frontotemporal lobar degeneration (FTLD), amyotrophic lateral sclerosis (ALS), and Alzheimer's disease (AD). However, there have been limited studies on whether there are any TDP-43 alterations in normal aging. We investigated TDP-43 distribution in different brain regions in normal aged ( n  =   3 for 26- or 36-month-old) compared to young ( n  =   3 for 6- or 12-month-old) mice. In both normal aged and young mice, TDP-43 and phosphorylated TDP-43 (pTDP-43) demonstrated a unique pattern of distribution in neurons in some specific brain regions including the pontine nuclei, thalamus, CA3 region of the hippocampus, and orbital cortex. This pattern was demonstrated on higher magnification of high-resolution double fluorescence images and confocal microscopy as mislocalization of TDP-43 and pTDP-43, characterized by neuronal nuclear depletion and cytoplasmic accumulation in these brain regions, as well as colocalization between TDP-43 or pTDP-43 and mitochondria, similar to what has been described previously in neurodegenerative disorders. All these findings were identical in both normal aged and young mice. In summary, TDP-43 and pTDP-43 mislocalization from nucleus to cytoplasm and their colocalization with mitochondria in the specific brain regions are present not only in aging, but also in young healthy states. Our findings provide a new insight for the role of TDP-43 proteinopathy in health and diseases, and that aging may not be a critical factor for the development of TDP-43 proteinopathy in subpopulations of neurons. Impact statement: Despite increasing evidence implicating the important role of TDP-43 in the pathogenesis of a wide range of age-related neurodegenerative diseases, there is limited study of TDP-43 proteinopathy and its association with mitochondria during normal aging. Our findings of cytoplasmic accumulation of TDP-43 that is highly colocalized with mitochondria in neurons in selective brain regions in young animals in the absence of neuronal loss provide a novel insight into the development of TDP-43 proteinopathy and its contribution to neuronal loss.